2008
DOI: 10.1016/j.jpeds.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Cocaine Exposure: Drug and Environmental Effects at 9 Years

Abstract: Persistent teratologic effects of CE on specific cognitive functions and additive effects of alcohol, lead, and marijuana exposure; IDA; and the home environment were identified. Documenting environmental factors in behavioral teratology studies is important, because in this sample, CE was associated with better home environment and lower environmental risk in a substantial number of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(131 citation statements)
references
References 26 publications
5
123
3
Order By: Relevance
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductionsupporting
confidence: 74%
“…We found a significant association between PCE and short-term memory (Richardson et al, 2009), and other researchers have reported deficits in specific areas such as verbal reasoning/memory (Bennett et al, 2002), executive function , cognitive processing/learning (Bridgett et al, 2011;Mayes et al, 2005Mayes et al, , 2007, visual spatial/math skills (Singer et al, , 2008, visual motor integration Schroder et al, 2004), and attention, inhibitory control, and impulsivity (Accornero et al, 2007;Bandstra et al, 2001;Bendersky et al, 2003;Carmody et al, 2011;Noland et al, 2005;Rose-Jacobs et al, 2009). However, there are also reports that show no negative effects of PCE on specific areas of cognition (Betancourt et al, 2011;Eyler et al, 2009;Hurt et al, 2009;Li et al, 2009;, and most groups, including ours, do not find a relation between PCE and global cognitive development (Accornero et al, 2007;Bandstra et al, 2002;Frank et al, 2005;Hurt et al, 1997Hurt et al, , 2001Messinger et al, 2004;Morrow et al, 2004Morrow et al, , 2006Singer et al, 2004).…”
Section: Introductionsupporting
confidence: 74%
“…Morrow et al (2006) reported IUCE was not associated with the Wechsler Individual Achievement Test-Second Edition (WIAT-II) or IQ at age 7; however, children with IUCE were 2.8 times more likely to have a learning disability. In contrast, Singer et al (2008) reported that at 9 years, achievement scores were associated with prenatal alcohol and marijuana, postnatal lead exposures, and home environment. IUCE was linked to perceptual reasoning.…”
Section: Introductionmentioning
confidence: 91%
“…Resolving the consequences of prenatal THC on human fetal brain development is complicated by variable THC exposures (dose, timing, and duration) between pregnancies, confounding exposures to multiple illicit drugs [29], and genotype-dependent effects [30]. Because neural cells differentiated from human-induced pluripotent stem cells (hiPSCs) most resemble fetal brain tissue [31,32,33,34], they provide an unprecedented platform for studying the molecular, cellular, and functional results of fetal THC exposure to neural cells, across a variety of genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%